Prediction of Response to Temozolomide in Low‐Grade Glioma Patients Based on Tumor Size Dynamics and Genetic Characteristics. (10th October 2015) - Mazzocco, P; Barthélémy, C; Kaloshi, G; Lavielle, M; Ricard, D; Idbaih, A; Psimaras, D; Renard, M‐A; Alentorn, A; Honnorat, J; Delattre, J‐Y; Ducray, F; et al.
Abstract : Both molecular profiling of tumors and longitudinal tumor size data modeling are relevant strategies to predict cancer patients' response to treatment. Herein we propose a model of tumor growth inhibition integrating a tumor's genetic characteristics (p53 mutation and 1p/19q codeletion) that successfully describes the time course of tumor size in patients with low‐grade gliomas treated with first‐line temozolomide chemotherapy. The model captures potential tumor progression under chemotherapy by accounting for the emergence of tissue resistance to treatment following prolonged exposure to temozolomide. Using information on individual tumors' genetic characteristics, in addition to early tumor size measurements, the model was able to predict the duration and magnitude of response, especially in those patients in whom repeated assessment of tumor response was obtained during the first 3 months of treatment. Combining longitudinal tumor size quantitative modeling with a tumor''s genetic characterization appears as a promising strategy to personalize treatments in patients with low‐grade gliomas.